(untitled) - Juras, Grzegorz (Akademia Wychowania Fizycznego w Katowicach)

Anticipatory Postural Adjustments in Dart Throwing

(untitled)
The aim of this study was to explore the effects of accuracy constraints on the characteristics of anticipatory postural adjustments (APA) in a task that involves a movement consisting of a controlled phase and a ballistic phase. It was hypothesized that APA scaling with task parameters (target size) would be preserved even when the task is performed by muscles that have no direct effects on APA. Sixteen healthy right handed subjects participated in the study. All participants had no prior experience in dart throwing. Subjects’ average age was 24.1 ± 1.9 years. A force platform and a motion capture system were used to register kinetics of the body and kinematics of the throwing arm and throwing accuracy. The experiment consisted of six series of twenty consecutive dart throws to a specified target. Target sizes (T2–T6) were set at 25%, 50%, 75%, 125% and 150% of target 1 (T1) initially set as the spread of the last 20 throws in a 50 throw training session. This allowed to distinguish six indexes of difficulty (ID’s) ranging from 2,9 to 5,9. A one-way ANOVA for repeated measures was used for statistical analysis. Results of ANOVA showed a significant effect of target size at Constant Error but no effect at APA time. There were also no significant differences between hit and miss throws. From a control perspective, it can be stated that changes in central commands did not lead to changes in APA time in the analyzed motor task.